Theoretical Research on Three-dimensional Cultivation of Poultry and Fruit and Vegetable Based on Photovoltaic Solar Greenhouse under the Background of New Energy - Li, Jiang (International Journal of Management and Education in Human Development, 2023)
"China's carbon dioxide emissions are expected to peak early by 2030, with the goal of becoming carbon neutral by 2060," said the U.S. -China Joint Statement on Climate Change released in Beijing on November 12, 2014. Therefore, on the basis of maintaining economic development, accelerating the optimization of industrial structure and energy structure, and developing new energy will become the main direction of China's current and future development. The "14th Five-Year Plan" is a new stage, critical period and window period for the development of China's solar energy industry, and the "two-carbon" policy will play an important role in the development of solar energy, solar energy and other renewable resources. The photovoltaic industry needs to take advantage of favorable development opportunities, reduce power generation costs, and continue to play an increasingly important role in achieving the two-carbon goal. In the new energy field, "clean and low-carbon" is the symbol of the new energy industry. Agriculture is a basic industry in China, which is related to national security and stability. Because "agriculture + new energy" project has become a new direction of agricultural development. "Agriculture + new energy" refers to the use of rural wasteland and wasteland to build photovoltaic power generation projects, with photovoltaic power generation on the top and economic agriculture on the bottom, "one land dual-use", improve the yield efficiency per mu of land, to achieve comprehensive utilization of land, in line with the national 145-carbon economic background, but also to assist the local county government to build a demonstration base for common prosperity. Therefore, the development of "agriculture + new energy" project is significant to local economic development, ecological and social benefits. With the rapid development of agriculture in our country, farming and husbandry will realize intensification and scale gradually. The progress of science and technology also drives the development of smart agriculture. In the breeding industry, it actively responds to the new development mode of the country's "two-carbon economy". In order to reduce labor costs and resource consumption, it is necessary to integrate environmental space and resources, use modern technology to improve the automation rate of aquaculture, improve the quality of aquaculture products, and achieve sustainable income and green agricultural development. Based on photovoltaic solar energy, this paper installs photovoltaic solar panels on the top of the traditional conservatory, divides the fruit and vegetable growing area and poultry breeding area inside the conservatory, and designs a three-dimensional farming mode based on solar energy and fruit, vegetable and poultry. By combining the three, we can make full use of breeding space and breeding resources. It not only saves geographical space, but also makes use of new energy. It uses poultry for fruit tree fertilizer, which not only saves costs, keeps the organic fruits and vegetables, but also realizes the continuous increase of profits, reduces carbon emissions and improves the profit rate of planting and breeding. To sum up, the project "three-dimensional breeding of poultry and fruits and vegetables based on photovoltaic solar greenhouse under the background of new energy" plays a positive role in promoting the development of national new energy cause as well as local social, economic and ecological construction, so it is of great significance to study and promote it.